The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.14295/cs.v10i4.3036
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tolerance to salt stress in soursop seedlings using hydrogen peroxide

Abstract: The exogenous use of hydrogen peroxide is an alternative in the acclimatization of plants to salt stress due to the greater activity of antioxidant enzymes. In this perspective, this study aimed to evaluate the gas exchange and the growth of soursop seedlings under salt stress using hydrogen peroxide. The study was conducted under greenhouse conditions. The treatments were distributed in randomized blocks, in a 5 x 2 factorial arrangement, related to five levels of electrical conductivity of the irrigation wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…53, 4.06, 3.43, 3.11, and 2.72 mm) were obtained with the method of application via seed soaking at salinity levels of 0.6, 1.2, 1.8, 2.4, and 3.0 dS m -1 , respectively. Silva et al (2019a) concluded that pre-treatment of seeds with H 2 O 2 attenuates the deleterious effects of irrigation water salinity on the stem diameter of soursop cv. 'Morada Nova' at 110 days after sowing a result similar to that found in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…53, 4.06, 3.43, 3.11, and 2.72 mm) were obtained with the method of application via seed soaking at salinity levels of 0.6, 1.2, 1.8, 2.4, and 3.0 dS m -1 , respectively. Silva et al (2019a) concluded that pre-treatment of seeds with H 2 O 2 attenuates the deleterious effects of irrigation water salinity on the stem diameter of soursop cv. 'Morada Nova' at 110 days after sowing a result similar to that found in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, several studies have evaluated the effects of hydrogen peroxide as an attenuator of salt stress, such as that of Silva et al (2016), who found that the application of H 2 O 2 in concentrations of 7 to 8 µM at Hydrogen peroxide attenuates salt stress in soursop seedlings application by foliar spraying and M4 -application by seed soaking + foliar spraying), in a 5 × 4 factorial arrangement, distributed in a completely randomized design, with four replicates and two plants per experimental unit, totaling 160 plants. The salinity levels used here were based on studies conducted by Silva et al (2019a).…”
Section: Treatmentsmentioning
confidence: 99%
“…SV 1 Stomatal conductance averages were 0.03 and 0.09 mol m -2 s -1 at the pre-flowering and fullflowering, respectively (Table 2). When the plant is put under stresses, the tendency is that the stomata close and, as a result, there is a reduction of transpiration to achieve a minimal loss of the water contained in the plant (SILVA et al, 2019). In addition, Schaffer et al (2009) infer that stomatal conductance is the main factor to control the net photosynthesis in mango trees, including with linear and exponential relations between these variables, due to a decrease in CO 2 supply to the mesophyll cells caused by stomatal closure, resulting in lower net photosynthetic rate (LAXMAN; ANNAPOORNAMMA; BIRADAR, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Among the alternatives that can be used to attenuate the stress caused by salinity on plants, the exogenous application of hydrogen peroxide -H 2 O 2 stands out (VELOSO et al, 2018;SILVA et al, 2019a;SILVA et al, 2020). H 2 O 2 can act as a key regulator in modulating the defense response of plants to salt stress, as its electrochemical characteristics enable it to cross membranes and spread between cell compartments, which facilitates its signaling function (SILVA et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…At low concentrations, H 2 O 2 regulates metabolism, cooperating with other hormones and signaling molecules, and confers tolerance to stress (SMIRNOFF; RNAUD, 2019). Silva et al (2019a), in a study evaluating the induction of tolerance to salt stress in soursop seedlings using H 2 O 2 , observed that the deleterious effects of water salinity on gas exchange and growth of soursop were mitigated by the exogenous application of H 2 O 2 . In another study, Silva et al (2020) concluded that foliar spraying of H 2 O 2 increased the tolerance of sunflower plants to salt stress, mainly due to the balance of ionic homeostasis and redox.…”
Section: Introductionmentioning
confidence: 99%